Carbon emission disclosure in Indonesia: Viewed from the aspect of board of directors, managerial ownership, and audit committee - Rifqi Nadhif Hafidh Simamora; Safrida; Sri Elviani (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2022)
This study aims to determine the effect of the board of directors on the disclosure of carbon emission, the effect of the managerial ownership on the disclosure of carbon emission, and the influence of the audit committee on disclosure of carbon emission in mining companies on the Indonesia Stock Exchange. The data sources used in this study are mining sector companies that have been listed on the Indonesia Stock Exchange (IDX) and have been published as sustainable annual financial reports for the period 2017 to 2020, and the data analysis used is multiple linear regression. The results of the study indicate that the board of directors has a positive and significant effect on disclosure of carbon emission; the managerial ownership has no significant effect on disclosure of carbon emission, and the audit committee has a positive and significant effect on disclosure of carbon emission.